Method for automatically identifying PRI patterns of complex radar signals. Issue 20 (13th September 2019) - Tang, Yuwen; He, Minghao; Tang, Xiaojie; Han, Jun; Fan, Xikun
Abstract : Aimed at the problem of automatically identifying pulse repetition interval (PRI) patterns of complex radar signals, a novel method is proposed in this paper. The roughness, normalised mean jump energy, and Sp‐ curve characteristic are extracted as feature set based on the analysis of PRI sequences in time domain. Finally, the decision tree is employed to recognise different PRI patterns. The simulation results show that the algorithm has high recognition accuracy and good robustness to spurious pulses and pulse missing.